Role of Damage-Associated Molecular Patterns and Uncontrolled Inflammation in Pediatric Sepsis-Induced Multiple Organ Dysfunction Syndrome - Alcamo, Alicia M.; Pang, Diana; Bashir, Dalia A.; Carcillo, Joseph A.; Nguyen, Trung C.; Aneja, Rajesh K. (Journal of Pediatric Intensive Care, 2019)
The incidence of multiple organ dysfunction syndrome (MODS) in sepsis varies from 17 to 73% and furthermore, increases the risk of death by 60% when controlled for the number of dysfunctional organs. Several MODS phenotypes exist, each unique in presentation and pathophysiology. Common to the phenotypes is the stimulation of the immune response by pathogen-associated molecular patterns (PAMPs), or danger-associated molecular patterns (DAMPs) causing an unremitting inflammation. Two of the MODS phenotypes are discussed in detail, thrombocytopenia-associated multiple organ failure (TAMOF) and the hyperinflammatory phenotype–macrophage activating syndrome (MAS) and hemophagocytic lymphohistiocytosis (HLH). In the end, we will briefly review the role of mitochondrial dysfunction as a significant contributor to the pathogenesis of MODS.
Keywords: pediatric severe sepsis; multiple organ dysfunction syndrome; pathogen-associated molecular patterns; danger-associated molecular patterns; macrophage activation syndrome; hemophagocytic lymphohistiocytosis